Evaluation of Industrial Buildings within the Scope of Renewal, Alsancak Tekel Warehouses - Yonca Yılmaz; Dilara Genç; Hümeyra Birol (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Industrial structures are cultural legacy sites in need of protection that carry the social, cultural, historical and architectural properties of their respective eras into the present day. Due to the changing production demands and technology, these structures lost their usage value and have been rendered obsolete. The interventions implemented and new functions provided to ensure the continuity of industrial structures must be in accordance with the character of the building. Our study focuses on the renovation process of one of the first industrial premises of the city of İzmir Alsancak Tekel Storages located in Port Rear Area. Industrial building history in the region dates back to the 1900s, when industrial and storage structures have been built. A new master development plan that entered into force in 1989, conserning the fate of these industrial buildings. As the result of the passed legislation, old tekel storages have been transformed to offices and cultural centres. In the scope of this study the changes that occurred in order to refunction the Alsancak Tekel Storages have been inspected. As a method, a detailed literature review of the history of the region was made, and data on the buildings examined before and after restoration were collected.